Assessing COVID-19-related health literacy and associated factors among school teachers in Hong Kong, China - Lau, Sam S. S.; Shum, Eric N. Y.; Man, Jackie O. T.; Cheung, Ethan T. H.; Amoah, Padmore Adusei; Leung, Angela Y. M.; Dadaczynski, Kevin; Okan, Orkan (Frontiers in Public Health, 2022)
Objectives: The COVID-19 pandemic developed rapidly, with changing guidelines, misinformation, inaccurate health information and rumours. This situation has highlighted the importance of health literacy (HL), especially among educators. The aims of this study were (i) to assess COVID-19-specific HL among school teachers in Hong Kong and (ii) to examine its association with demographic factors, self-endangering work behaviours (i.e. work intensification, work extensification and work quality reduction), secondary burnout symptoms (i.e. exhaustion related to work and psychosomatic complaints), the level of knowledge of COVID-19- or pandemic-related information and the level of confusion about COVID-19-related information. Methods: A self-report survey was administered to 366 school teachers from April 2021 to February 2022. COVID-19-specific HL was measured using the HLS-COVID-Q22. Self-endangering work behaviour scales (i.e. extensification of work, intensification of work and work quality reduction) and two dimensions of the Burnout Assessment Tool (i.e. psychosomatic complaints and exhaustion) were also used for assessment. Data were analysed using an independent samples Student’s t-test, analysis of variance, correlation analysis and adjusted multilinear regression models. Results: The results showed that 50.8% of teachers had sufficient HL, 38.3% had problematic HL and 10.9% had inadequate HL. The HL did not vary by sex, but varied according to the type of school, the weekly working hours and the number of students attending the school. Teachers with sufficient HL scored significantly lower for two types of self-endangering work behaviour – intensification of work (p = 0.003) and work quality reduction (p = 0.007) – than those with insufficient HL. After excluding those who had already been vaccinated, respondents with sufficient HL felt more positive about COVID-19 vaccination than those with insufficient HL (t[180] = 4.168, p < 0.001). Teachers with sufficient HL felt more informed (p < 0.001) and less confused (p < 0.001) about COVID-19-related information than those with insufficient HL. Multiple linear regression analysis revealed that age (β = 0.14, p = 0.011) and the weekly teaching hours (β = -0.206, p < 0.001) were significant predictors of HL. Conclusions: The findings may serve as a guide for addressing health literacy gaps among school teachers.